The warm compress of clove water (syzygium aromaticum) therapy during bouts of acute gouty arthritis - Rita Sari; Janu Purwono; Desi Safitri; Pira Prahmawati; Nur Hasanah (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Non-communicable diseases keep increase numbers in both developed and developing countries such as gout arthritis. Gouty arthritis is an inflammation of the joints caused by high levels of uric acid in the blood (hyperuricemia). Most people with gout arthritis complain of pain in the joints.Purpose: To determine the effect of cloves water warm compress  (syzygium aromaticum) on reducing pain among elderly with gouty arthritisMethod: This study used a quasi-experimental pre and post test without control (self-control) with 11 participants. The data analysis used was the Dependent T test. As for preparing the ingredients, using 5 grams of cloves boiled with 300 cc to boil, let stand for about 1-3 minutes until a warm temperature (45 - 50 0C), then observe / measure the patient's pain level.After measuring the pain scale, then apply a compress using a clean cloth on the affected joint for 20 minutes, then measure the pain scale again. This action performs every evening (once) at bedtime repeatedly for 5 consecutive days.Results: Showed that the intensity of pain before intervention was 6.73 and the average pain intensity after intervention was 3.00. The result of the t-test is 14,907 with a p-value of 0,000 <α (0.05).Conclusion: The effect had a significantly greater reduction in pain by clove water warm compresses among elderly with gouty arthritis.